2018
DOI: 10.33837/msj.v1i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Identificação fenotípica e genotípica de cepas de estafilococos oriundas de uma unidade de abate de aves

Abstract: Vários tipos de alimentos são implicados em intoxicações gastrointestinais por Staphylococcus aureus, sendo frequentemente relacionado com carne e derivados, devido às propriedades de atividade de água, pH, nutrientes e a extensiva manipulação destes alimentos durante o processamento. Este trabalho teve por objetivo identificar cepas potencialmente toxigênicas de Staphylococcus isoladas de diferentes nichos em uma unidade de abate de frango de corte, bem como avaliar a resistência à diferentes antimicrobianos.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…(ATCC 14458 and ATCC 29213) showed inhibition halos between 6 and 37 mm, being resistant to ampicillin, cefazolin and amoxicillin + clavulanate and equally sensitive to vancomycin, clidamycin and azithromycin. Ferreira et al (2015) identified potentially toxigenic strains of Staphylococcus isolated from different critical points in a broiler slaughter unit, as well as assessed the resistance of these strains to different antimicrobials. Most isolates were resistant to sulfonamide (98.5%), nalidixic acid (89.3%) and penicillin G (87.70%).…”
Section: Discussionmentioning
confidence: 99%
“…(ATCC 14458 and ATCC 29213) showed inhibition halos between 6 and 37 mm, being resistant to ampicillin, cefazolin and amoxicillin + clavulanate and equally sensitive to vancomycin, clidamycin and azithromycin. Ferreira et al (2015) identified potentially toxigenic strains of Staphylococcus isolated from different critical points in a broiler slaughter unit, as well as assessed the resistance of these strains to different antimicrobials. Most isolates were resistant to sulfonamide (98.5%), nalidixic acid (89.3%) and penicillin G (87.70%).…”
Section: Discussionmentioning
confidence: 99%
“…Food poisoning by Staphylococcus spp. is considered the second most commonly reported foodborne illness (BRASIL, 2016), being a common cause of intoxication due to the ingestion of food contaminated with staphylococcal enterotoxins (SES) produced during bacterial multiplication (FERREIRA et al, 2018). According to WONG; BERGDOLL (2002), the amount of enterotoxin needed to cause poisoning is less than 1 µg.…”
Section: Introductionmentioning
confidence: 99%